Beyond interferons: Non-canonical roles of MITA/STING - Liting Zhang; Chuchu Zhang; Junjie Zhang (Cell Insight)
Mediator of IRF3 activation (MITA)/Stimulator of Interferon Genes (STING) (also known as MPYS/ERIS) is a crucial adaptor protein for initiating antiviral innate immune responses to intracellular DNA and DNA viruses. MITA binds cGAMP, a second messenger synthesized by cGAS in response to intracellular DNA, culminating in the induction of type I interferons (IFNs), inflammatory cytokines, and interferon-stimulated genes (ISGs). While the canonical IFN-dependent MITA signaling has been extensively studied, recent research has unveiled a growing repertoire of IFN-independent functions of MITA in various physiological processes and pathological conditions. These non-canonical roles of MITA are increasingly recognized for their involvement in critical processes such as antiviral activity, senescence, autophagy, metabolism, lysosomal biogenesis, and the development of neurological disorders. In this review, we summarize the latest advances in understanding MITA's non-canonical functions and provide insights into key scientific questions that remain to be addressed. Deciphering how MITA is involved in these complex physiological and pathological processes will not only deepen our understanding of MITA signaling, but may also offer new therapeutic targets for treating related diseases.